Intraocular foreign body (IOFB) - Ahmad Ikliluddin; Listya Normalita (Universitas Muhammadiyah Surabaya, 2023)
Intraocular foreign bodies (IOFBs) were 16-40% of open globe trauma and could cause severe visual loss. Therefore, they require immediate diagnosis and treatment. This is a case of an 18-year-old man who came to the hospital complaining of a metal piercing in his left eye while cutting some metal about 2 hours before entering the hospital. On ophthalmologic examination, visual acuity of the left eye was 3/60, and a full-thickness laceration of the cornea with an IOFB was seen at the anterior chamber base. Immediate IOFB evacuation was carried out on the same day as the incident happened. During the operation, a metal intraocular foreign body with a sharp tip, 4x2x1 mm in size, was successfully removed in intact condition. Next, the laceration and the corneal limbus incision were sutured using 10.0 nylon. The stitches are tight, and the anterior chamber depth is maintained. Evaluation on the fourth week after IOFB evacuation showed that visual acuity in the left eye was 6/20 with lens correction C-1.50 x 150Â° become 6/7.5. Appropriate and prompt diagnosis and management of open eye injury can contribute to preserving a good anatomical and functional result.